IoT and AI for Silambam Martial Arts: A Review - Ramanathan, Vijayarajan; T, Meyyappan; Natarajan, Gnanasankaran (EAI Endorsed Transactions on Internet of Things, 2024)
Silambam is a traditional martial art from Tamil Nadu, India. It is a stick-fighting art that has been practiced for centuries. In recent years, there has been growing interest in using technology to enhance the practice and promotion of Silambam. One way to do this is to use the Internet of Things (IoT). IoT devices can be used to collect data on Silambam practitioners' movements and performance. This data can then be analysed using artificial intelligence (AI) to provide insights and recommendations to practitioners. For example, IoT sensors could be attached to Silambam sticks to track the number of rotations, speed, and force of each strike. This data could then be used to provide feedback to practitioners on their technique and progress. AI could also be used to develop personalized training programs for Silambam practitioners. For example, AI could analyse a practitioner's data to identify areas where they need improvement and then recommend specific exercises or drills. In addition to enhancing the practice of Silambam, IoT and AI could also be used to promote the art to a wider audience. For example, IoT-enabled Silambam sticks could be used to create interactive training games or simulations. Overall, IoT and AI have the potential to revolutionize the way that Silambam is practiced and promoted. By using these technologies, we can make Silambam more accessible, engaging, and effective for practitioners of all levels.
Keywords: Silambam; Internet of Things; Artificial Intelligence; Machine Learning